PAL‐mediated SA biosynthesis pathway contributes to nematode resistance in wheat. (3rd June 2021) - Zhang, Haili; Huang, Qiulan; Yi, Ling; Song, Xiaona; Li, Lin; Deng, Guangbing; Liang, Junjun; Chen, Fang; Yu, Maoqun; Long, Hai
Summary: The pathogen cereal cyst nematode (CCN) is deleterious to Triticeae crops and is a threat to the global crop yield. Accession no. 1 of Aegilops variabilis, a relative of Triticum aestivum (bread wheat), is highly resistant to CCN. Our previous study demonstrated that the expression of the phenylalanine ammonia lyase (PAL) gene AevPAL1 in Ae. variabilis is strongly induced by CCN. PAL, the first enzyme of phenylpropanoid metabolism, is involved in abiotic and biotic stress responses. However, its role in plant–CCN interaction remains unknown. In the present study, we proved that AevPAL1 helps to confer CCN resistance through affecting the synthesis of salicylic acid (SA) and downstream secondary metabolites. The silencing of AevPAL1 increased the incidence of CCN infection in roots and decreased the accumulation of SA and phenylalanine (Phe)‐derived specialized metabolites. The exogenous pre‐application of SA also improved CCN resistance. Additionally, the functions of PAL in phenylpropanoid metabolism correlated with tryptophan decarboxylase (TDC) functioning in tryptophan metabolism pathways. The silencing of either AevPAL1 or AevTDC1 exhibited a concomitant reduction in the expression of both genes and the contents of metabolites downstream of PAL and TDC. These results suggested that AevPAL1, possibly in coordination with AevTDC1, positively contributes to CCN resistance by altering the downstream secondary metabolites and SA content in Ae. variabilis . Moreover, AevPAL1 overexpression significantly enhanced CCN resistance in bread wheat and did not exhibit significant negative effects on yield‐related traits, suggesting that AevPAL1 is valuable for the genetic improvement of CCN resistance in bread wheat. Significance Statement: The cereal cyst nematode (CCN) constrains wheat yield and yet few CCN‐resistant genes have been reported in wheat. The use of genes from wheat relatives is an efficient strategy to improve wheat CCN resistance. AevPAL1 from Aegilops variabilis was found to play an essential role in CCN resistance through coordinately functioning with AevTDC1 to affect salicylic acid and phenylalanine‐derived metabolite biosynthesis. The overexpression of AevPAL1 in bread wheat enhanced CCN resistance without significant yield penalty, suggesting that AevPAL1 is valuable for genetic improvement in CCN resistance.